Applicability of 99mTc‐Labeled Human Serum Albumin Scintigraphy in Dogs With Protein‐Losing Enteropathy. (21st February 2017) - Engelmann, N.; Ondreka, N.; von Pückler, K.; Mohrs, S.; Sicken, J.; Neiger, R.
Abstract : Background: Diagnosis of protein loss into the gastrointestinal tract using noninvasive techniques is challenging. In people, scintigraphy not only is a sensitive tool to confirm protein‐losing enteropathy (PLE), but it also allows for localization of protein loss. Hypothesis/Objectives: To investigate the feasibility of 99m Tc‐labeled human serum albumin (HSA) scintigraphy in dogs with PLE in comparison with control dogs. Animals: A total of 8 clinically healthy control research dogs and 7 client‐owned dogs with gastrointestinal clinical signs and hypoalbuminemia (serum albumin concentration <2.0 g/dL). Methods: Prospective case–control study. After IV injection of 400 MBq freshly prepared 99m Tc HSA (30 mg/dog), images of the abdomen were obtained 10, 60, 120, and 240 minutes postinjection. Additional images of the salivary and thyroid glands were obtained to rule out free 99m Tc. A scan was considered positive for PLE when radiopharmaceutical exudation was detectable in the intestinal tract. Results: Only 1 control dog showed exudation of the radiopharmaceutical into the intestinal tract. No free 99m Tc was detected in any dog. In dogs with PLE, focal small intestinal and diffuse small intestinal radiopharmaceutical exudation into the bowel was detected in 2 and 3 dogs, respectively, whereas in 2 dogs, there was disagreement about whether radiopharmaceutical exudation was focal or diffuse. Conclusion and Clinical Importance: 99m Tc‐labeled HSA scintigraphy was feasible to diagnose PLE in dogs.